Middle East and North Africa Quarterly Economic Brief, January 2015 Plunging Oil Prices - Devarajan, Shantayanan (Middle East and North Africa Economic Monitor, 2015)
In the three months since most observers, including the World Bank, issued their last forecasts, the Middle East and North Africa (MENA) Region has changed substantially. Political tensions have eased somewhat with presidential and legislative elections completed in a few countries. Egypt's cabinet approved the electoral constituencies' law, the last step before calling for the House of Representatives elections, the final milestone in the political roadmap initiated in July 2013. Presidential elections were held in Tunisia, with Beji Caid Essebsi sworn in as the new president in December. Iran's nuclear talks with the P5+1 were extended for 6 months--while bilateral talks continueâ€"with the aim of reaching a deal in July 2015. In Iraq, the government and the Kurdish region reached an agreement in December resolving a longstanding dispute over the budget and distribution of oil revenues. Meanwhile, Lebanon, Yemen and Libya still struggle to maintain a functional government. The global economy is estimated to have expanded by 2.6 percent (q/q annualized rate), better than the second quarter of 2014, but unchanged from the slow pace seen in 2012 and 2013. But the most important development is that international oil prices have literally collapsed, reaching a level below